2021
DOI: 10.1007/s00778-021-00671-8
|View full text |Cite
|
Sign up to set email alerts
|

Managing bias and unfairness in data for decision support: a survey of machine learning and data engineering approaches to identify and mitigate bias and unfairness within data management and analytics systems

Abstract: The increasing use of data-driven decision support systems in industry and governments is accompanied by the discovery of a plethora of bias and unfairness issues in the outputs of these systems. Multiple computer science communities, and especially machine learning, have started to tackle this problem, often developing algorithmic solutions to mitigate biases to obtain fairer outputs. However, one of the core underlying causes for unfairness is bias in training data which is not fully covered by such approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 163 publications
0
36
0
Order By: Relevance
“…At present, in the research process of mental health assessment and analysis of a large number of college students in China, due to the current situation of different regional cultures and different family economic levels, there will be problems of analysis difficulty and inaccurate analysis [5]. It is difficult for scholars at home and abroad to deal with the group of college students in the research of psychology, because this stage of college students is a stage of rapid change in life and prominent life process, so the research situation is more one-sided and concentrated, and there is no general, comprehensive, universal, and all-round research on college students' mental health [6]. Biswas et al found that the current mental health status of college students is closely related to their environment, their own pressure, man-machine communication relationship, family economic level, and other factors.…”
Section: The Related Workmentioning
confidence: 99%
“…At present, in the research process of mental health assessment and analysis of a large number of college students in China, due to the current situation of different regional cultures and different family economic levels, there will be problems of analysis difficulty and inaccurate analysis [5]. It is difficult for scholars at home and abroad to deal with the group of college students in the research of psychology, because this stage of college students is a stage of rapid change in life and prominent life process, so the research situation is more one-sided and concentrated, and there is no general, comprehensive, universal, and all-round research on college students' mental health [6]. Biswas et al found that the current mental health status of college students is closely related to their environment, their own pressure, man-machine communication relationship, family economic level, and other factors.…”
Section: The Related Workmentioning
confidence: 99%
“…As the world increasingly becomes data-driven and machine-learning evaluated, it is essential to anticipate issues of bias and fairness, and proactively devise ways to counter existing and entrenched biases in data collection methods 20 21. Logging transparent data, in deliberately designed data structures, is likely to help address harmful and ethically dubious recommendations and conclusions based on biased data 21 22…”
Section: Transactions Across a Power Differentialmentioning
confidence: 99%
“…Data-driven decision support systems have been accused of being a fertile ground to produce biased results, thus leading to discriminatory decisions [1]. As historical data often encode biases [2] explicitly or implicitly [3], pattern recognition algorithms inevitably relate their predictions with protected characteristics such as race or gender.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, more than 20 definitions of fairness [4] and respective bias metrics have been proposed. However, existing metrics express different and often contradictory notions of fairness [5,6,7] depending on local legal and cultural conventions [8] or on the type of decisionsupport system [1]. Deciding which metric is most appropriate for the task at hand is difficult [9] as several parameters need to be considered such as causal influences among features, misrepresentation of groups and different modalities of data [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation